Etiolofia, epidemiologia e prognóstico das pneumonias associadas à ventilação mecânica em um hospital de ensino, com ênfase no estudo molecular e virulência de Staphylococcus aureus - Bonesso, Mariana Fávero [UNESP] (2015)
Ventilator associated pneumonia (VAP) is the first cause of hospital acquired infections in patients in Intensive Care Units (ICU). The most frequent infectious agents isolated in VAP are Staphylococcus aureus, Pseudomonas aeruginosa and Acinetobacter baumannii, which vary according to the hospital. S. aureus methicillin resistant (MRSA) is frequently found in hospital environment, additionally this specie carry several virulence factors responsible to tissue invasion. Thereby, the aim of this work was verify the influence of host factors as well as the microbiologic factors in pneumonia outcome with emphasis in S. aureus genetic study. The study design was a cohort study including patients in the first 48 hours of mechanical ventilation and followed up twice a week for up to 8 weeks. More profound analysis was conducted for S. aureus isolates accessing the resistance profile, clonal characteristics by PFGE, sequence type by MLST, virulence by PCR, protein A and alpha toxin expressions by Western Blot, HPLC for PSM expressions. S. aureus was the most isolated specie in ICU and 66% of the isolates were causing respiratory infections. The frequency of MRSA in our ICU was 43% and the SCCmec types were I (4%), II (78%) e IV (17%). The most frequent virulence factors were icaA, hla e hld. The clonal profile of strains isolated from VAP showed a variety of strains not clustered. The most frequent sequence types in this study were ST105, ST5 and ST398. Independent risk factors for S. aureus VAP were PSMbeta 2 production, the presence of sea gene and solid cancer, while the presence of hlb and sea genes were associated to death. Trauma was the only predictor factor associated to VAP. Regarded to the stratification according to pathogen type, we found that trauma was a risk factor to S. aureus VAP and also for Enterobacteriacea, which also included belonging to female gender and presenting central nervous system disease. Age and steroids usage ...